Ministry Of Investment and International Cooperation Decree No. 256 Of The Year 2018 Amending Certain Provisions of the Executive Regulations of the Law On Joint Stock Companies, Partnerships Limited By Shares, Limited Liability Companies and One Person Companies, Promulgated By Decree No. 96 of the Year 1982 = وزارة الاستثمار والتعاون الدولى قرار رقم 256 لسنة 2018 بتعديل بعض أحكام اللائحة التنفيذية لقانون شركات المساهمة وشركات التوصية بالأسهم والشركات ذات المسئولية المحدودة وشركات الشخص الواحد الصادرة بقرار رقم 96 لسنة 1982 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic